Determinants of Audit Quality - Surtikanti, S; Supriyanto, J (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
A public accountant has an obligation in providing good audit quality but with the case of freezing the license of the public accounting firm karana violation of SPAP, the public began to doubt the quality of the audit itself. The purpose of this study is to empirically test the quality of audits influenced by audit fees and audit quality influenced by the audit agreement period. The methods used are descriptive and verifikative. The population is 16 Public Accounting Firms in bandung area, using saturated sampling techniques or census, while the respondents are senior auditors, partners. Statistical testing uses correlation analysis, multiple regression analysis, coefficient of determination and to test the hypothesis then used t test. The results showed that the quality of audit is influenced by the audit fee, between the quality of the audit and the audit fee has a positive relationship which means that when the audit fee is large, the quality becomes better. The quality of audit is also influenced by the period of auditor’s alliance and has a negative relationship where when the alliance period becomes long, the audit quality becomes poor, the quality of the audit is also influenced by other factors that are not researched such as independence, competence, professionalism and so on. Based on the results of the study the authors suggest that when accepting work from clients, the approved audit fee must be adjusted to the audit fee structure so that the quality is better and the complexity of the services provided while the contracting period with the client should be the second year of auditing the auditing team of auditors in rotation to keep the audit quality good.